Using Topomer Comparative Molecular Field Analysis to Elucidate Activity Differences of Aminomethylenethiophene Derivatives as Lysyl Oxidase Inhibitors: Implications for Rational Design of Antimetastatic Agents for Cancer Therapy. (16th May 2020) - Han, Jing; Yan, Guochao; Feng, Jianping; Yang, Xianglin; Zhou, Yuan
Abstract : Topomer comparative molecular field analysis (topomer CoMFA) is applied to the quantitative structure-activity relationship (QSAR) study of aminomethylenethiophene (AMT) derivatives as lysyl oxidase (LOX) inhibitors. A total of thirty-six AMT derivatives were selected to build the QSAR model. The established topomer CoMFA model has the non-cross-validated correlation coefficient ( r 2 ) of 0.912 and the leave-one-out correlation coefficient ( q 2 ) of 0.540, which is statistically significant. The theoretically predicted anti-LOX potency agrees well with the experimentally observed inhibitory activity, proving the reasonable predictive ability of the QSAR model. The effect of molecular field information on the LOX inhibition of substituted aminomethylenethiophene was discussed in detail. The structural modification of the aminomethylenethiophene scaffold was carried out, and novel AMT derivatives with theoretically decent LOX inhibition were proposed. The topomer CoMFA modeling could provide a quantitative perspective into the structure-activity relationship of AMT derivatives and potentially speed up the rational design of LOX inhibitors as antimetastatic agents for cancer therapy.